Pengaruh Electronic Word Of Mouth (E-Wom) Dan Content Marketing Terhadap Impulse Buying Pada Aplikasi Tiktok (Studi Kasus Pada Mahasiswa Di Kecamatan Lowokwaru Malang) - Hartanto, Widya Miranda Putri; Malikah, Anik; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study examines the influence of Electronic Word of Mouth (E-Wom) and Content Marketing on Impulse Buying on the TikTok application, focusing on students in Lowokwaru District, Malang. This study aims to determine the influence of E-Wom and Content Marketing on Impulse Buying, along with the development of technology and the increasing use of social media, impulsive shopping among generation Z is increasing. Through a quantitative approach, by collecting data using a questionnaire distributed to 110 student respondents in Malang City, then the data that has been collected is analyzed using SPSS software. The results of this study indicate that Electronic Word of Mouth (E-Wom) and Content Marketing simultaneously have a significant influence on Impulse Buying on the TikTok application. Partially, E-Wom shows a stronger influence than Content Marketing on Impulse Buying. Keywords: E-Wom, Content Marketing, Impulse Buying, TikTok, Students.